Determinan Perubahan Laba : Ditinjau dari Rasio-Rasio Keuangan (Studi pada Perusahaan yang Tergabung di JII ) (Equilibrium: Jurnal Ekonomi Syariah, 2020)
This study examines the effect of Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TATO), and Return on Assets (ROA) on changes in earnings. The research focuses on companies that are members of the Jakarta Islamic Index (JII) 2015-2018 and have positive profits, and periodically publish their financial reports. Data analysis using multiple linear regression method. The results showed that the current ratio had no significant effect on changes in earnings. This means that the current rate is an inability to predict company profits due to the ineffective value of existing assets or current liabilities. The debt-equity ratio has a significant effect on earnings. This means that the higher the DER is a signal that shows creditor confidence in paying debt increases, which indicates that the ability to generate profits also increases. Total assets turnover has no significant effect on changes in earnings. This means that total asset turnover is an inability to predict changes in earnings. This is because the use of assets to support sales is still not optimal. Return on assets has no significant effect on wages. This is related to the inability to return on investments to predict changes in earnings. A large number of assets should have a high contribution to the production process.